International acquisitions of Chinese firms - Deng, Ping (Henry Stewart Talks, 2013)
Chinese multinational corporations (MNCs), Outward foreign direct investment (FDI), Cross-border mergers and acquisitions (M&As), International acquisitions, Strategic assets, Absorptive capacity, Chinese government, Political economy, National security issues, Institutional theory, Resource-based theories